Association between surgical wait time and hospital length of stay in primary total knee and hip arthroplasty. (2nd August 2021) - Seddigh, Shahriar; Lethbridge, Lynn; Theriault, Patrick; Matwin, Stan; Dunbar, Michael J.
Abstract : Aims: In countries with social healthcare systems, such as Canada, patients may experience long wait times and a decline in their health status prior to their operation. The aim of this study is to explore the association between long preoperative wait times (WT) and acute hospital length of stay (LoS) for primary arthroplasty of the knee and hip. Methods: The study population was obtained from the provincial Patient Access Registry Nova Scotia (PARNS) and the Canadian national hospital Discharge Access Database (DAD). We included primary total knee and hip arthroplasties (TKA, THA) between 2011 and 2017. Patients waiting longer than the recommended 180 days Canadian national standard were compared to patients waiting equal or less than the standard WT. The primary outcome measure was acute LoS postoperatively. Secondarily, patient demographics, comorbidities, and perioperative parameters were correlated with LoS with multivariate regression. Results: A total of 11, 833 TKAs and 6, 627 THAs were included in the study. Mean WT for TKA was 348 days (1 to 3, 605) with mean LoS of 3.6 days (1 to 98). Mean WT for THA was 267 days (1 to 2, 015) with mean LoS of 4.0 days (1 to 143). There was a significant increase in mean LoS for TKA waiting longer than 180 days (2.5% (SE 1.1); p = 0.028). There was no significant association for THA. Age, sex, surgical year, admittance from home, rural residence, household income, hospital facility, the need for blood transfusion, and comorbidities were all found to influence LoS. Conclusion: Surgical WT longer than 180 days resulted in increased acute LoS for primary TKA. Meeting a shorter WT target may be cost-saving in a social healthcare system by having shorter LoS. Cite this article: Bone Jt Open 2021;2(8):679–684.